Entrepreneurship : frameworks and empirical investigations from forthcoming leaders of European research - Wiklund, Johan (Advances in entrepreneurship, firm emergence and growth, 2006)
Among the major ways researchers think about research topics and approaches, the lesson of these ten chapters by many of the "new breed" of European entrepreneurship researchers is that those values and world-views which have traditionally been the hallmark of the European approach, remain evident as the underpinnings of the "new breed" approach. In doing so, the field of entrepreneurship will grow in terms of the range of ideas, data sources, and techniques. It will also grow more competitive, initially through the addition of new people, but as their ideas begin to gain traction, as differin.